404. Surveillance of Clostridioides difficile Burden in Hospitals Through Wastewater Analysis. (15th December 2022) - Au, Emily; Waddell, Barbara Jean M; Acosta, Nicole; Du, Kristine; Chavarriaga, Maria Bautista; McCalder, Janine; Doorn, Jennifer Van; Low, Kashtin; Lu, Xuewen; Chekouo, Thierry; Dai, Xiaotian; Cabaj, Jason; et al.
Abstract: Background: New tools capable of dynamic assessment of the varying burden of Clostridioides difficile infections are required to mitigate increased patient morbidity, mortality, and health costs. Wastewater (WW)-based epidemiology (WBE) is an emerging science, enabling comprehensive, inclusive, and unbiased assessment of populations, spatially and temporally. We sought to detect, quantify and track C. difficile across a range of scales using WBE. Methods: WW collected from two hospitals; the Rockyview General Hospital (RGH; 600 beds) and Peter Lougheed Centre (PLC; 550 beds) both based in Calgary, were compared to that from a municipal WW Treatment Plant (WWTP) in Calgary, Canada. DNA was extracted from pellets collected after WW centrifugation. A multiplexed quantitative PCR assay was used to quantify the abundance of C. difficile 16S rRNA and toxin A (tcdA ) genes. These were then assessed as raw values or as normalized ratios to three fecal biomarker genes: total bacterial 16S rRNA, human 18S rRNA, and Bacteroides HF183 16S rRNA. Kruskal-Wallis and Mann-Whitney tests were performed using RStudio and GraphPad Prism (version 9.3.1). Results: Eight weekly samples collected from the RGH demonstrated significant changes in the levels of total C. difficile 16S rRNA gene and tcdA over time (P=0.0004 and P=0.0005, respectively, Kruskal-Wallis). Similar trends in total C. difficile and tcdA burden over time were observed when gene copies were normalized with the three fecal biomarker genes. Over a separate 13-week comparison, C. difficile and tcdA gene target abundance was greater in hospital WW (RGH and PLC) than in community-based samples from the WWTP (P=0.048 and P=0.012, respectively, Mann-Whitney). There was no significant difference in C. difficile and tcdA gene target abundance between RGH and PLC (P=0.896 and P=0.343, respectively, Mann-Whitney). Clostridioides difficile genes in wastewater measured by quantitative PCR. C. difficile 16S rRNA and tcdA gene abundance normalized as a ratio against total bacterial load (16S rRNA) varies over time and is markedly increased in hospitals relative to a municipal wastewater treatment plant in Calgary, Canada. Conclusion: WW surveillance is a powerful tool that can monitor the burden the C. difficile across a range of scales in real-time. This tool could augment infection prevention and control and antimicrobial stewardship programs to better understand factors that contribute to colonization and infection. Disclosures: Thomas J. Louie, MD, Artugen: Advisor/Consultant|Artugen: Grant/Research Support|Crestone: Advisor/Consultant|Crestone: Grant/Research Support|Finch Therapeutics: Advisor/Consultant|Finch Therapeutics: Grant/Research Support|Rebiotix: Advisor/Consultant|Rebiotix: Grant/Research Support|Seres Therapeutics: Advisor/Consultant|Seres Therapeutics: Grant/Research Support|summit plc: Advisor/Consultant|summit plc: Grant/Research Support|Vedanta Biosciences: Advisor/Consultant|Vedanta Biosciences: Grant/Research Support.